Listen in terror : British horror radio from the advent of broadcasting to the digital age - Hand, Richard J. (Book collections on Project MUSE., 2014)
A full-length study of British horror radio from the pioneering days of recording and broadcasting right through to the digital audio cultures of our own time. It offers an historical, critical and theoretical exploration of horror radio and audio performance examining key areas such as writing, narrative, performance practice and reception throughout the history of that most unjustly neglected of popular art forms: radio drama and 'spoken word' auditory cultures.